2021
DOI: 10.1017/wet.2021.36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of row spacing and herbicide programs for control of glyphosate-resistant Palmer amaranth (Amaranthus palmeri) in dicamba/glyphosate-resistant soybean

Abstract: Glyphosate-resistant (GR) Palmer amaranth is one of the most difficult to control weeds in soybean production fields in Nebraska and the United States. An integrated approach is required for effective management of GR Palmer amaranth. Cultural practices such as narrow row spacing might augment herbicide efficacy for management of GR Palmer amaranth. The objectives of this study were to evaluate the effect of row spacing and herbicide programs for management of GR Palmer amaranth in dicamba/glyphosate-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Since 2017, XtendFlex crop varieties with traits conferring resistance to dicamba (3,6‐dichloro‐2‐methoxybenzoic acid) plus glyphosate ( N ‐[phosphonomethyl] glycine) have been commercialized for cotton, corn, and soybean (Allen et al., 2021). This newer herbicide‐resistant crop technology allows the application of dicamba formulations alone or in combination with glyphosate in cotton, corn, and soybean, and their adoption is increasing (McDonald et al., 2021). Currently, XtendFlex cotton, corn, and soybean varieties are widely adopted in the southeastern United States, with dicamba regularly applied in combination with glyphosate to control problematic weed species, including Palmer amaranth ( Amaranthus palmeri S. Watson) and to broaden the weed control spectrum including grasses (Blanchett et al., 2015; Leon et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2017, XtendFlex crop varieties with traits conferring resistance to dicamba (3,6‐dichloro‐2‐methoxybenzoic acid) plus glyphosate ( N ‐[phosphonomethyl] glycine) have been commercialized for cotton, corn, and soybean (Allen et al., 2021). This newer herbicide‐resistant crop technology allows the application of dicamba formulations alone or in combination with glyphosate in cotton, corn, and soybean, and their adoption is increasing (McDonald et al., 2021). Currently, XtendFlex cotton, corn, and soybean varieties are widely adopted in the southeastern United States, with dicamba regularly applied in combination with glyphosate to control problematic weed species, including Palmer amaranth ( Amaranthus palmeri S. Watson) and to broaden the weed control spectrum including grasses (Blanchett et al., 2015; Leon et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Results of the meta-analysis indicate that the benefits of narrow row spacing may likely be achieved with PRE fb POST herbicide application compared with PRE or POST-only or POST fb POST herbicide application, as weed densities may be high due to emergence during the early season (in the case of POST-only, and POST fb POST) or resurgence (in the case of PRE-only) during the late season. For example, McDonald et al (2021) reported 3 to 32 versus 123 to 497 plants m −2 of A. palmeri with PRE fb POST versus POST-only herbicide programs in a soybean row-spacing study conducted in Nebraska. However, the weed density data set had only one study each for PRE (Johnson and Hoverstad 2002) and POST fb POST herbicide application (McDonald et al 2021); therefore, no definitive conclusion could be drawn.…”
Section: Resultsmentioning
confidence: 99%
“…For example, McDonald et al (2021) reported 3 to 32 versus 123 to 497 plants m −2 of A. palmeri with PRE fb POST versus POST-only herbicide programs in a soybean row-spacing study conducted in Nebraska. However, the weed density data set had only one study each for PRE (Johnson and Hoverstad 2002) and POST fb POST herbicide application (McDonald et al 2021); therefore, no definitive conclusion could be drawn.…”
Section: Resultsmentioning
confidence: 99%
“…Palmer amaranth has a fluctuating emergence pattern that is affected by light, moisture, and temperature; it can germinate rapidly, completely germinating in 1 d under ideal conditions (Jha et al 2010;Jha and Norsworthy 2009;Spaunhorst 2016;Steckel et al 2004); and has a unique long emergence period that varies geographically based on the length of the local growing season. In the southeastern United States, Palmer amaranth emerges from May to September, and in the Midwest it emerges from May to August (McDonald et al 2021). Palmer amaranth has evolved resistance to many herbicide modes of action (Heap 2021).…”
Section: Introductionmentioning
confidence: 99%